Performance comparison of linear controllers for voltage dip mitigation using dynamic voltage restorer - Hatif Bin Abdul Majeed (00000118652); Dr Hassan Abdullah Khalid (Islamabad : USPCAS-E, 2018)
TH-89
Keywords: MS-ESE Thesis MS Thesis